USE OF INDUCTIVE METHODS IN THE EDUCATIONAL PROCESS - Mirazimova Mukhabat Normatovna (Web of Journals Publishing, 2024)
The article mentions the importance of using inductive methods in the educational process and the possibilities of increasing the effectiveness of education.
Keywords: Inductive methods, interview method, preschool education, training, modern education, education and upbringing, pedagogue, technological maps.